Impact of less social connectedness and fear of COVID-19 test on employees task performance: A multi-mediation model - Zhang, Yueman (Frontiers in Public Health, 2022)
The core objective of this study is to examine the impact of less social connectedness and testing fear on employee health. This study also investigates the mediating role of psychological strain between the relationship of less social connectedness, testing fear and employee health. Furthermore, this study also assesses the impact of employee health on employee performance. The study's target audience consisted of employees in the electronics industry in China. The convenience sample method was used in this study to collect data from respondents. Data analysis of this study was performed by using the structural equation modeling technique. The statistical software used for data analysis is Smart PLS 3. The results of this study show that less COVID-19 testing fear has a negatively significant impact on employee health, but less social connectedness has not significant direct impact on employee health. Furthermore, psychological strain was discovered to mediate the relationship between less social connectedness and employee health and testing fear and employee health. In addition, this impact of employee health on employee performance was found significant. This study provides theoretical and practical implications. In the context of practical implications, this study provides valuable insights for the organizational management to develop a healthy and positive working environment and adopt healthy behavior among their employees which ultimately foster their job performance.